Book reviews - Mikalauskas, Ignas (Transformations In Business & Economics, 2024)
Dalia STREIMIKIENE, Asta MIKALAUSKIENE, Gabija STANISLOVAITYTE (2023), Corporate Social Hypocrisy. CSR in the Era of Global Crises, Taylor & Francis, New York, 194 p.
Keywords: -